Beyond territory: dynamic geographies of knowledge creation, diffusion, and innovation - Bathelt, Harald; Feldman, Maryann P.; Kogler, Dieter F. (Regions and cities, 2011)
"The main purpose of the book is to discuss new trends in the dynamic geography of innovation and argue that in an era of increasing globalization, two trends seem quite dominant: rigid territorial models of innovation, and localized configurations of innovative activities. The book brings together scholars who are working on these topics. Rather than focusing on established concepts and theories, the book aims to question narrow explanations, rigid territorializations, and simplistic policy frameworks; it provides evidence that innovation, while not exclusively dependent on regional contexts, can be influenced by place-specific attributes. The study of innovation encompasses an increasingly wide and rich field of conceptual and empirical studies and debates, which span across disciplinary boundaries in the social sciences. This book identifies the key debates, new streams of inquiry and progress in research related to the transfer, circulation and generation of knowledge in a spatial perspective. The book is organized into three subheadings: place-specific aspects of specialization and diversity; evolutionary spatio-sectoral dynamics; and bridging the local and the global divide. It is the aggregate of all of these contributions that offers an exclusive insight into the dynamic geographies of knowledge creation, diffusion and innovation, well beyond the traditional territorial approach. This volume contains new empirical and conceptual work by an interdisciplinary group of leading scholars from areas such as economic geography, innovation studies, and political science"--
Enth. 13 Beitr
Keywords: Konjunkturtheorie; Technologietransfer; Globalisierung